Avaliação dos efeitos da oxigenoterapia hiperbárica no processo de cicatrização de peritoniostomia com prótese sintética: estudo experimental em animais (Rattus norvegicus albinos) com uso de tela de polipropileno - Faion, Adilson Gomes (2017)
To analyze macroscopically and microscopically the effects of hyperbaric oxygen therapy in the inflammatory and healing process in the abdominal wall area of rats (Rattus norvegicus albinus) submitted to laparostomy, in contact with a synthetic prosthesis (polypropylene mesh). Rationale: To assess within a biological experimental model the effect of hyperbaric oxygen therapy in tissues in contact with a synthetic prosthesis. Methods: Twenty-four male Rattus norvegicus albinus from the Vivarium of the Surgical Technique Laboratory of the Faculty of Medicine of the Federal University of Uberlândia, with a minimum age of 3 at 5 months and weight of 250 at 375 grams, were randomly divided into two groups: study (A e B) (n = 12) e four sub groups whit n=6 (Al e A2 and BI e B2). The group A underwent two types of treatment: hyperbaric oxygen therapy sessions with followup until process completion in three days A1 or five days (A2). The animals were evaluated macroscopically regarding their pre- and post-operative weight and the degree of adherence regarding the presence of infectious processes in the laparostomy area and presence of fistulas and/or abscesses, pre- and post-operative weight changes, and the degree of adherence. Furthermore, the same animals were also microscopically evaluated, measuring four variables: microscopic examination of inflammatory infiltrates using hematoxylin-eosin (HE); examination of inflammation in scar tissue using HE; examination using Masson's trichrome staining for evaluating the fibrosis process; and examination using Picrosirius staining for evaluating the type of collagen fibers. Results: For evaluation we used the Kruskal-Wallis test with p-value simulated using Monte Carlo from 10,000 samples, the Mann-Whitney test, and the chi-square test. Results: The test results indicate that there is no difference (at the 5% level) among the four groups concerning the five variables evaluated. Conclusion: The analysis of the various macroscopic parameters and using microscopic image analysis showed no statistically significant benefits or harmful effects, in any of the groups studied, in the use of hyperbaric oxygen therapy in these specific conditions.